2022
DOI: 10.1371/journal.pone.0279340
|View full text |Cite
|
Sign up to set email alerts
|

The association between social factors and COVID-19 protective behaviors and depression and stress among midwestern US college students

Abstract: Purpose The aim of this cross-sectional study was to examine the relationship between social factors and COVID-19 protective behaviors and two outcomes: depressive and perceived stress symptoms. Methods In September 2020, 1,064 randomly selected undergraduate students from a large midwestern university completed an online survey and provided information on demographics, social activities, COVID-19 protective behaviors (i.e., avoiding social events and staying home from work and school), and mental health sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…26,27 Furthermore, these findings are supported by studies suggesting that the major lesion sites in the neural circuit model of depression are related to the self-referential function, and that dysfunction within and between important structures in this circuit can induce disturbances in emotional behavior and other cognitive aspects of depressive syndromes in humans. 28 Our study found that lack of contact with people close to them, which is recommended to prevent psychological problems, was correlated with depressive symptoms. The causal relationship between social contact and depressive symptoms is unclear, although a correlation is observed.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…26,27 Furthermore, these findings are supported by studies suggesting that the major lesion sites in the neural circuit model of depression are related to the self-referential function, and that dysfunction within and between important structures in this circuit can induce disturbances in emotional behavior and other cognitive aspects of depressive syndromes in humans. 28 Our study found that lack of contact with people close to them, which is recommended to prevent psychological problems, was correlated with depressive symptoms. The causal relationship between social contact and depressive symptoms is unclear, although a correlation is observed.…”
Section: Discussionmentioning
confidence: 56%
“…Studies have shown that negative cognitions in depression are associated with low empathy [ 25 ], but contrasting views have been noted about the relationship between empathy and depression [ 26 , 27 ]. Furthermore, these findings are supported by studies suggesting that the major lesion sites in the neural circuit model of depression are related to the self-referential function, and that dysfunction within and between important structures in this circuit can induce disturbances in emotional behavior and other cognitive aspects of depressive syndromes in humans [ 28 ].…”
Section: Discussionmentioning
confidence: 72%
“…Pandemic and related restrictions were associated with reductions in physical activity and increases in phone use as well as increases in depression and anxiety symptoms among college students (Mack et al, 2021). During this time, housing and financial stress, lower social engagement or support, and lower family functioning (Garcia Colato et al, 2022; Généreux et al, 2021; Kreski et al, 2022; Wiedemann et al, 2022) were also associated with worse mental health symptoms or psychological distress as people coped with the dramatic pressures of job instability, remote work and school, social isolation, and functioning in home environments not designed for the multiple requirements of that period. Longitudinal research during the resolution of acute pandemic challenges showed return to previous levels of symptoms (Jia et al, 2021); specifically, these newly emerged mental health symptoms returned to prepandemic levels (Graupensperger et al, 2022).…”
Section: Role Of the Covid-19 Pandemicmentioning
confidence: 99%
“…Since the onset of COVID-19, understanding the mental health of college students has been at the forefront, more specifically, perceived stress [35,36] and depression [37][38][39][40]. Perceived stress has been quantified using the PSS-10 among college students based on eating behaviors [41,42], anxiety and sleep [43], levels of food insecurity [44], exercise [45], smartphone addiction [46], physical activity and sleep [47], online learning [48], and diet and emotional eating [49] among undocumented students [50] and student-athletes [51].…”
Section: Introductionmentioning
confidence: 99%